Is education in Poland really effective? - Biernacki, Marek; Czesak-Woytala, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
This paper discusses the results of the Programme for International Student Assessment and the results obtained by students of the Wroclaw University of Economics. Special emphasis was placed on mathematics. Polish students obtained much better results in the latest PISA edition in maths, science and reading when compared to previous editions and to the average results calculated for the OECD countries. Despite this fact the scores of Polish students in the Creative Problem Solving test were much worse than the average for the OECD countries. It is worth noting that the Polish education system has been undergoing dynamic changes which are correlated with political changes and with the increase of social need for participating in decision-making in the education of the young generations. Unfortunately, the pressure to achieve good results in exams means that teachers have started to teach test solving instead of problem solving. This was also shown in the edition of the PISA exam. The authors of the article propose to change the structure of the didactic process, especially at universities, in a way that would make it possible to increase the number of exercises and laboratory hours.
Didactics of Mathematics, 2013, Nr 10 (14), s. 5-18
Keywords: effectiveness of mathematics education; PISA; Programme for International Student Assessment